Effect of the Essential Oil of Minthostachys verticillata (Griseb.) Epling and Limonene on Biofilm Production in Pathogens Causing Bovine Mastitis - Cerioli, María F.; Moliva, Melina V.; Cariddi, Laura N.; Reinoso, Elina B. (Frontiers in Veterinary Science, 2018)
Bovine mastitis causes large annual economic losses around the world. Different microorganisms are associated with the disease. The capacity of pathogens to adhere to bovine mammary epithelial cells is associated with biofilm production which leads to antibiotic resistance. Research is now leading to search alternative control methods and medicinal plants constitute a natural, safe, effective and inexpensive option. Minthostachys verticillata is an autochthonous medicinal plant of Argentina with multiple ethnobotanical properties. In a previous study, we demonstrated that the essential oil (EO) of this species and limonene, one of its compounds, inhibited the growth of mastitis pathogens. The objective of the present work was to determine the inhibitory effect of the essential oil of M. verticillata and limonene, on biofilm formation and on mature biofilm produced by pathogens isolated from bovine mastitis. Time kill assay and bacterial lysis were also determined. Furthermore, RAPD-PCR assays were performed to determine changes in bacterial DNA after EO and limonene exposition. Bacterial isolates were identified as Escherichia coli (EC3 and EC9), Bacillus pumilus (BP5, BP6 and BP7) and Enterococcus faecium (EF1) by rRNA 16S sequencing and MALDI-TOF MS. All the strains were able to form biofilm. Addition of both lactose and sucrose did not affect biofilm production. MIC values for EO were 3.6 mg/ml for E. faecium; 0.9 mg/ml for E. coli (EC3), 14.5 mg/ml for E. coli (EC9),1.8 mg/ml for B. pumilus (BP7), 3.63 mg/ml for B. pumilus (BP6) and 29.0 mg/ml for B. pumilus (BP7). MIC values for limonene were 6.6 mg/ml for B. pumilus (BP6) and 105 mg/ml for B. pumilus (BP5). These results demonstrated that EO was more effective than limonene, showing also bactericidal action against E. faecium (minimal inhibitory concentration (MBC) = 29.0 mg/ml). This result was corroborated by time of death assay, observing a cell decrease after at 6 h, and then by bacterial lysis assay. Both EO and limonene affected mature biofilm of isolated strains. The results contribute to the study of EO and limonene which may serve as a therapy against bovine mastitis pathogens inhibiting the development of pathogenic bacteria.